Development of Tutoring E-Modules Through Metacognitive Strategies to Improve Self-Regulated Learning for Junior High School Students - Farikhah Yuniarti; Budi Astuti (AL-ISHLAH: Jurnal Pendidikan, 2022)
Education is a business or activity operated intentionally, regularly, and planned to develop desired behavior. This study aims to (1) produce a metacognitive strategy e-module that can improve junior high school students' self-regulated learning, (2) produce an appropriate metacognitive strategy e-module to improve junior high school students' self-regulated learning, (3) examine the effectiveness of using e-media media. This research is a Research and Development (RD) research using the five states of ADDIE model such as analysis, design, development, implementation, and evaluation. This study involved 40 VIII graders and 7 Guidance and Counselling teachers in South Cilacap Subdistrict. The results of the study show the developed E-module is classified as "Very Appropriate" by the media and material experts to be used as a supporting media to improve self-regulated learning for junior high school students. In addition, the e-module used is effective to support learning activities based on the measurement of the self-regulated learning of junior high school students, with the results of an increase in self-regulated learning of junior high school students. This development research resulted in an appropriate metacognitive strategy e-module that could improve students' self-regulated learning. Thus, it can be concluded that the metacognitive strategy e-module is feasible and effective enough to be used to improve the self-regulated learning of junior high school students.